Role of a Novel, Fresh-Frozen Cellular Bone Allograft in Lumbar Interbody Spinal Fusion - Charles P. Nolte; Arjun Singh; Aaron Ishmael; Caleb Wipf; Jingdian Huang; Andriy Noshchenko; Vikas Patel (Clinical Spine Surgery, 2026)
Study Design: Retrospective matched-cohort study. Objective: To evaluate the clinical efficacy, safety, and economic impact of a novel cellular bone allograft (PrimaGen Advanced Allograft; CBA-P) used in combination with recombinant human bone morphogenetic protein-2 (rhBMP-2) for short-segment lumbar interbody fusion. Summary of Background Data: Osteobiologic grafts are increasingly used to optimize lumbar interbody fusion outcomes. Recombinant human bone morphogenetic protein-2 (rhBMP-2) improves fusion rates but is costly and associated with complications. Cellular bone allografts (CBAs) aim to enhance fusion by providing a bony scaffold, growth factors, and viable cells, but their clinical and economic benefit remains unclear. Methods: We retrospectively assessed 100 adults who underwent 1- or 2-level posterior or transforaminal lumbar interbody fusion between 2017 and 2023. Fifty patients received CBA-P with rhBMP-2 (experimental cohort), and 50 matched controls received rhBMP-2 with standard-of-care demineralized bone matrix and/or allograft bone powder. Matching was based on age decade, sex, and fusion level. The primary outcome was interbody fusion at 12 and 24 months, assessed using a validated radiograph measurement platform. Secondary outcomes included revision surgery, complications, pain scores, and per-case osteobiologic cost. Results: Fusion rates were similar between cohorts at 12 months (95.7% vs. 89.1%, P =0.27) and 24 months (100% vs. 89.5%, P =0.49), with comparable revision and complication rates. Estimated blood loss (364.4 vs. 232.9 mL, P